Analisis Faktor-Faktor Yang Mempengaruhi Price Earning Ratio Pada Perusahaan Lq 45 - Asteria, Beta (JURNAL RISET MANAJEMEN SEKOLAH TINGGI ILMU EKONOMI WIDYA WIWAHA PROGRAM MAGISTER MANAJEMEN, 2016)
This research deals with the impact of Price Book Value (PBV), Debt Equity Ratio (DER), and Return on Assets (ROA) to Price Earning Ratio (PER) of LQ 45 company. Methods of collecting data through purposive sampling. The number of companies are 45. But only 39 companies inclued in sample from 2011 to 2014. The data utilized in this research is panel data. Total of samples are 156. This research utilizes the data from Indonesia Stock Exchange (IDX). The model used in this research is multiple regressions. The independent variables are Price Book Value (PBV), Debt Equity Ratio (DER), and Return on Assets (ROA). Meanwhile, the dependent variable is Price Earning Ratio (PER). The research findings show that Price Book Value (PBV), Debt Equity Ratio (DER) dan Return On Asset (ROA) give the significant impact partially and simultaneusly on Price Earing Ratio (PER) at real level 5 percent. All independent variables explain 22.73 percent of Price Earing Ratio (PER) while the rest 72.20 percent is explained by other variables. Keywords: Price Earing Ratio (PER), Price Book Value (PBV), Debt Equity Ratio (DER) dan Return On Asset (ROA).